Character Education Value in Dongkrek Art Performance: A Study of The Enculturation Process in The Madiun Regency Community - Annisa Imsawati Sugiyanto; Sri Marmoah; Sandra Bayu Kurniawan (Universitas Sebelas Maret, 2024)
This research describes the values of Dongkrek art as one of the complementary learning resources in improving the practice of character education through the Pancasila student profile strengthening project. The purpose of the research is to describe the character values of Dongkrek art. The research type is descriptive qualitative. Data were collected through literature review and field observation. The results showed that Dongkrek art is categorized as a local art consisting of a combination of music, dance, vocal, and literary elements. The character values come from the dance movements, the character of the actors through the masks, and the musical instruments. The character values that can be included in character education are spiritual, spirituality, moral, symbolic, patriotism or heroism, leadership, welfare or social care, justice, and aesthetics.